LEGAL ANALYSIS OF DISCIPLINARY SANCTIONS BY TEACHERS TO STUDENTS AT SCHOOL - Miarsa, Fajar Rachmad Dwi; Santoso, Hardi Anugrah; Amalia, Tita; Saputra, Beni (PT. Altin Riset Publishing, 2024)
Education has a vital role in shaping the character and quality of human resources, with student discipline as one of the key elements in creating a conducive learning environment. This study aims to analyze the law related to the granting of disciplinary sanctions by teachers to students in schools, focusing on the legal challenges faced by teachers in enforcing discipline. Through a normative juridical approach, this study examines the Supreme Court Decision Number 1554 K/Pid/2013 which affirms that teachers cannot be punished when carrying out their professional duties, including in the provision of disciplinary sanctions. In addition, regulations such as Articles 39 and 40 of Government Regulation No. 19 of 2017 provide a legal basis for teachers to enforce discipline without fear of legal consequences. As such, the study highlights the importance of legal protection and the development of clear policies to support effective and safe education efforts.